Growth Hormone Promotes in vitro Maturation of Human Oocytes - Li, Yue; Liu, Hui; Yu, Qingqing; Liu, Hongbin; Huang, Tao; Zhao, Shigang; Ma, Jinlong; Zhao, Han (Frontiers in Endocrinology, 2019)
Increasing the success rate of in vitro maturation (IVM) for human oocytes has a major clinical significance. Previous studies have shown that growth hormone (GH) added into IVM medium could promote IVM of oocytes from non-human beings. However, few studies on systematic IVM for human oocytes with GH have been reported. Human germinal vesicle (GV) oocytes collected for IVM were cultured with different concentrations of GH to optimize the concentration. Metaphase II (MII) stage oocytes obtained from IVM were fertilized by intracytoplasmic sperm injection (ICSI). Maturation rate, fertilization rate, and blastocyst rate were assessed after IVM with or without GH. Furthermore, gene expression profiles were compared in oocytes between the two groups using single cell RNA-seq. The optimal concentration of GH for IVM was 200ng/ml, and the maturation rate of this group reached 70% which was double of the control group (35%, P = 0.004). The fertilization rate (73.1% vs. 60.3%) and blastocyst rate (25.0% vs. 15.5%) both had an increasing trend in the GH group compared to controls. Single cell RNA-Seq and real-time PCR data showed that GH could significantly enhance the expression of genes associated with meiotic progression and embryo development, such as AURKA (aurora kinase A, P = 0.007), PDIA6 (protein disulfide isomerase family A member 6, P = 0.007), LINGO2 (leucine rich repeat and Ig domain containing 2, P = 0.007), and CENPJ (centromere protein J, P = 0.039). Taken together, GH could promote maturation of human oocytes, probably through accelerating meiotic progression, balancing redox homeostasis of cellular environment, and promoting oocyte developmental competence.